The effect of neutrophil to lymphocyte ratio (NLR), lymphocyte to monocyte ratio (LMR) and mean platelet volume to thrombocyte ratio (MPV/PLT) on survival in myelodysplastyc syndrome (Annals of Medical Research, 2022)
Aim: The aim of the study is to evaluate the relationship between age and leukocyte subtype ratio and their effects on survival in patients diagnosed with myelodysplastic syndrome (MDS).Methods: We retrospectively examined total of 101 patients diagnosed with MDS between January 2010 and June 2020. The patients were analysed by dividing into two groups;
Keywords: myelodysplastic syndrome; lymphocyte/neutrophil ratio; lymphocyte/monocyte ratio